Analysis of Use of Feeders to Minimize Lightning Strikes on Medium Voltage Networks - Eko Vernando Siregar (Journal of Science Technology (JoSTec), 2021)
Electricity no could separated with life society . Benefit energy electricity for life man very a lot of source lighting and needs other . By because that very required reliability in electrical energy delivery from center generator power electricity until to consumer . A proper protection system is needed could prevent happening damage in particular on feeder 20 kv . Frequent things occur for example occur disturbance strike lightning that can result in damage and cut off delivery of electrical energy . By because that for prevent happening disturbance caused _ by lightning the eat coordination safety lightning (arrester) must conducted with good . PT PLN ( Persero ) Pematang Area Siantar is a service unit serving customers needs electricity in the area Pematang Siantar and surrounding. PT PLN ( Persero ) Pematang Area Siantar also To do care , and repair on network voltage medium 20 kV distributed from substation parent to consumer.